FISCAL POLICY UNDER CONDITIONS OF GLOBAL RISKS AND ECONOMIC UNCERTAINTY - Kachula, Svitlana (SWorld-Ger Conference proceedings, 2025)
Defining the place and role of budgetary policy under conditions of global risks and economic uncertainty has become increasingly relevant, as contemporary challenges – from pandemics to geopolitical conflicts – fundamentally transform traditional approac